Imaging of congenital pulmonary malformations - Praticò, Francesco Emanuele; Corrado, Michele; Della Casa, Giovanni; Parziale, Raffaele; Russo, Giuseppe; Gazzani, Silvia Eleonora; Rossi, Enrica; Borgia, Daniele; Mostardi, Maurizio; Bacchini, Emanuele; Cella, Simone; De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2016)
Congenital pulmonary malformations represent a broad spectrum of anomalies that may result in varied clinical and pathologic pictures, ranging from recurrent pulmonary infections and acute respiratory distress syndrome, which require timely drug therapy, up to large space-occupying lesions needing surgical treatment. This classification includes three distinct anatomical and pathological entities, represented by Congenital Cystic Adenomatoid Malformation, Bronchopulmonary Sequestration and Congenital Lobar Emphysema. The final result in terms of embryological and fetal development of these alterations is a Congenital Lung Hypoplasia. Since even Bronchial Atresia, Pulmonary Bronchogenic Cysts and Congenital Diaphragmatic Hernias are due to Pulmonary Hypoplasia, these diseases will be discussed in this review (1, 2).